Reflections on Communication and Sport: On Strategic Communication and Management. (March 2013) - Pedersen, Paul M.
In this essay, Paul M. Pedersen provides a personal reflection on communication and sport and examines the area of strategic communication and management. His assessment begins with an overview of the growth and significance of the sport industry and communication's ubiquitous and influential roles within it. In tracing his scholarly journey, Pedersen comes to see communication as an essential element in the sport industry, whether viewed from individualistic, organizational, or sport-specific perspectives. The focus section in this essay examines research on the Strategic Sport Communication Model (SSCM) and its usefulness in categorizing and operationalizing the field from a strategic management perspective. Using the SSCM as the guide, this reflection provides examples of sport communication research focused on each of the model's three components. The reflection concludes with an analysis of future research opportunities, particularly opportunities to explore strategic decisions and effectiveness in the sport industry's use of new/social media. Pedersen concludes that a key to developing best communication practices will be a research agenda that more fully contextualizes strategic communication and management in the sport marketplace.